Comments on the Logistic Function in ROC Analysis: Applications to Breast Cancer Detection - Goin, J. E.; Haberman, Joann D. (Methods of Information in Medicine, 1982)
ROC analysis is rapidly becoming the method of choice for determining the performance of diagnostic imaging techniques. This discussion is intended to provide scientists working in diagnostic imaging with a more in-depth view of the detection task analysis than is currently available in the statistical methodology literature. The logistic function is defined and its utility is illustrated by analyzing two breast cancer detection modalities.
Keywords: ROC Analysis; Signal Detection; Diagnostic Imaging; Logistic Function; Breast Cancer Detection